219k views
2 votes
Given f(x)=2x + 5 and g(x)=x^2 - 3

f(3)=
g(2)=
g(f(-1))=
f(g(-1))=
g(f(x))=

User Jon Harmon
by
5.0k points

1 Answer

3 votes

Answer:

See below

Explanation:

Given

  • f(x)=2x + 5 and
  • g(x)=x^2 - 3

=================

f(3)

  • f(3)= 2*3 + 5 = 11

g(2)

  • g(2)= 2^2 - 3 = 1

g(f(-1))= 6

  • f(-1) = -2 + 5 = 3
  • g(3) = 3^2 - 3 = 6

f(g(-1))= 1

  • g(-1) = (-1)^2 - 3 = -2
  • f(-2) = -2*2 + 5 = 1

g(f(x))

  • g(f(x))= (2x +5)^2 - 3 = 4x^2 + 20x + 25 - 3 = 4x^2 + 20x + 22
User Bedir Yilmaz
by
4.9k points